Estetsko občutenje - Tomc, Gregor (Časopis za kritiko znanosti, 1999)
Unlike emotions and thoughts, feelings represent a psychological experience with which we reply to questions on the level of pleasing and revolting. The aesthetic experience presupposes a special group of feelings with which we respond to questions arising on the sub-level of the beautiful and ugly. It isa complex multidimensional space in the mind which we create all our lives and with which we respond to sense impulses from our environment (mostly visual and aural) and endogenous mental constructs which indirectly originate in our senses. The impulses of the beautiful-ugly sub-level which trigger comfort in us are recognised as aesthetic phenomena.
Keywords: aesthetics; estetika; estetski doživljaj; duševnost; občutki